The protective effects of resveratrol pretreatment in cyclophosphamide-induced rat ovarian injury: an vivo study. (3rd October 2021) - Nie, Zhaoyan; Zhang, Lei; Chen, Wei; Zhang, Yanan; Wang, Wei; Hua, Rui; Zhang, Tiantian; Zhao, Chunfang; Gong, Miao; Wu, Haifeng
Abstract: Objectives: To explore whether resveratrol (Res) pretreatment could exert a protective effect on cyclophosphamide (Cy) induced ovarian toxicity in a rat model. Methods: Twenty-four female 7-week old Sprague-Dawley rats were randomly divided into four groups: Con, administered with vehicle solutions; Cy, treated with Cy; Res + Cy, treated with Cy + Res combined; Res, treated with Res. After 21 d of treatments, the rats were euthanized and blood samples were collected to evaluate the levels of anti-Müllerian hormone (AMH). The Ovaries were processed for immunohistochemical and western blotting. Results: Cy-treat caused the decrease of body weights and ovarian weight. AMH was lower in Cy group, whereas AMH levels were similar among other groups. Histomorphology showed a large number of primordial follicles were activated in Cy groups, whereas the primordial follicles were inhibited in the Res and Res + Cy groups. The expressions of Sirt1, Foxo3a were up-regulated and p53, Caspase-3, and Bax were down-regulated in Res + Cy and Res groups ( p  < .05). Conclusions: Res can prevent the primordial follicle activation and decrease apoptosis induced by Cy. Res may be an effective protection for ovarian function during chemotherapy, which means a new nonsurgical application for protection of ovarian reserve.